2010
DOI: 10.1177/0363546509356976
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Results of Single-Tunnel Coracoclavicular Ligament Reconstruction Using Autogenous Semitendinosus Tendon

Abstract: Single-tunnel CC reconstruction with an autogenous hamstring tendon graft after a mean follow-up of 33 months (range, 18-47) appears to be a satisfactory means of treating acute Rockwood type IV, V, chronic type III, and painful nonunited distal clavicle fractures with CC separation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(65 citation statements)
references
References 31 publications
3
60
0
2
Order By: Relevance
“…Several other authors have found similar results after ACCR with tendon grafts. [32][33][34][35][36][37][38][39][40] In our study the mean ASES score improved from 58.9 preoperatively to 93.8 postoperatively, with a high median patient satisfaction rating of 9 of 10.…”
Section: Discussionsupporting
confidence: 50%
“…Several other authors have found similar results after ACCR with tendon grafts. [32][33][34][35][36][37][38][39][40] In our study the mean ASES score improved from 58.9 preoperatively to 93.8 postoperatively, with a high median patient satisfaction rating of 9 of 10.…”
Section: Discussionsupporting
confidence: 50%
“…Loss of reduction in clinical series ranges between 15 and 80 % [19][20][21][22]. Not all patients are symptomatic, and the decision for revision should be based on patient's symptoms and not on radiographic findings.…”
Section: Complications From Operative Treatment Of Acromioclavicular mentioning
confidence: 99%
“…Weighted stress radiographs of the AC joint have been used to differentiate a type II from an occult type III injury, 41 but studies indicate that these views do not improve the diagnostic accuracy of this injury. 93 The AP radiograph of the shoulder is best used for evaluating vertical CC translation, and the axillary radiograph best identifies posterior dislocations (Fig. 4).…”
Section: Radiographic Evaluationmentioning
confidence: 99%
“…Although this technique uses a semitendinosus graft, its biomechanical characteristics are dependent on the three #5 Ethibond sutures, which have biomechanical characteristics similar to those of other rigid fixation techniques. 93 Endobutton (flip-button) device techniques for CC ligament repair have been reported to provide satisfactory outcomes through open and arthroscopic techniques (Fig. 9).…”
Section: Ca Ligament Transfermentioning
confidence: 99%